Penerapan Model Pembelajaran Snowball Throwing Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas XI IPS 3 SMA Negeri 1 Gianyar - Sudarma, I Nyoman (Metta : Jurnal Ilmu Multidisiplin, 2022)
This study aims to improve learning activities and learning outcomes in the subject of Hinduism and Virtue Education for Class XI IPS 3 students of SMA Negeri 1 Gianyar Odd Semester 2022/2023 Academic Year, through the Snowball Throwing (ST) learning model. The research method used is Action Research. Class (PTK) which consists of 2 cycles. The research subjects were 33 students of class XI IPS 3 at SMA Negeri 1 Gianyar for the academic year 2022/2023. Data analysis used comparative descriptive techniques by comparing learning outcomes in the initial conditions with learning outcomes in each cycle, and qualitative descriptive analysis by comparing the results of observation and reflection in cycle I and cycle II. With the application of learning Snowball Throwing to the Basic Competency of yoga asana According to Hindu Susastra in class XI IPS 3 SMA Negeri 1 Gianyar 2022/2023 academic year, it can be seen that at the end of cycle I there has been an increase in average class learning outcomes of 0.12% that is, from the initial average of 60.25 to 69.39, and the average student learning activity was 84.84% and in cycle II there was an increase of 0.60 from the average class learning outcomes of 69.39 to 80.33 and the activity student learning reaches 100%. While the overall learning completeness of students at the end of cycle II, there was an increase of 0.72%. Thus, class XI IPS 3 SMA Negeri 1 Gianyar experienced an increase in learning activities and learning outcomes in the Basic Competence of yoga asana in Hindu Literature.